2012
DOI: 10.1371/journal.pone.0049940
|View full text |Cite|
|
Sign up to set email alerts
|

CD4+ Cells Regulate Fibrosis and Lymphangiogenesis in Response to Lymphatic Fluid Stasis

Abstract: IntroductionLymphedema is a chronic disorder that occurs commonly after lymph node removal for cancer treatment and is characterized by swelling, fibrosis, inflammation, and adipose deposition. Although previous histological studies have investigated inflammatory changes that occur in lymphedema, the precise cellular make up of the inflammatory infiltrate remains unknown. It is also unclear if this inflammatory response plays a causal role in the pathology of lymphedema. The purpose of this study was therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
217
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 189 publications
(243 citation statements)
references
References 25 publications
16
217
1
9
Order By: Relevance
“…By comparing tissues harvested from mice that had undergone axillary lymph node dissection with a more severe model of lymphatic injury in the mouse tail, we have also shown that the degree of adipose deposition is related to the severity of lymphatic obstruction and tissue inflammation (6). The association between inflammation and adipose deposition is important and supported by our previous studies demonstrating that depletion of T cells or blockade of T-helper type 2 (Th2) cell inflammation potently inhibits adipose tissue deposition in the mouse-tail model (6,40). However, although it is evident that inflammatory changes are necessary for adipose deposition in lymphedema, it remains unclear which inflammatory pathways regulate adipose homeostasis in lymphedematous tissues.…”
supporting
confidence: 55%
See 4 more Smart Citations
“…By comparing tissues harvested from mice that had undergone axillary lymph node dissection with a more severe model of lymphatic injury in the mouse tail, we have also shown that the degree of adipose deposition is related to the severity of lymphatic obstruction and tissue inflammation (6). The association between inflammation and adipose deposition is important and supported by our previous studies demonstrating that depletion of T cells or blockade of T-helper type 2 (Th2) cell inflammation potently inhibits adipose tissue deposition in the mouse-tail model (6,40). However, although it is evident that inflammatory changes are necessary for adipose deposition in lymphedema, it remains unclear which inflammatory pathways regulate adipose homeostasis in lymphedematous tissues.…”
supporting
confidence: 55%
“…Matched tissue biopsies were obtained from the normal and lymphedematous upper extremity of patients with post-surgical lymphedema (grades I-III; see below) by Professor Waldemar Olszewski at the Polish Academy of Science. Full-thickness (5 mm) skin biopsies were fixed, paraffinembedded, and sectioned at a thickness of 5 m using our previously described methods (40). The Institutional Review Boards (IRB) of the Polish Academy of Science and Memorial Sloan-Kettering Cancer Center (MSKCC) approved all studies.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations